Influence of Teachers Characteristics on Provision of Psychosocial Support to Girls Infected or Affected by HIV and AIDS - Ngithi , Mbutitia Francisca; Kafu , Patrick; Shikuku, Mulambula (African Journal of Education,Science and Technology (AJEST), 2014)
The need to address the provision of psychosocial support to girls infected or affected by HIV and AIDS in schools necessitated this study. The study focused on teachers‟ characteristics that influence the provision of psychosocial support to girls infected or affected by HIV and AIDS. The study sampled 148 teachers from 21 primary schools, 8 secondary schools and one special institution. From these learning institutions 294 girls were sampled for the study. Data was collected using questionnaire. The χ2 (CHI-SQUARE) was used to establish the influence of teachers characteristics and provision of psychosocial support to girls infected or affected by HIV and AIDS psychosocial stressors. The hypotheses were tested at alpha level of 0.05. The teachers‟ characteristics considered by the study were sex, working experience and designation. The study established that sex, working experience and designation have significant influence on psychosocial support provided by teachers to girls infected or affected by HIV and AIDS. The study established that teachers provided mainly instrumental information but were not conversant with the provision of emotional psychosocial support. The findings can be used as a basis by stakeholders to strategize on development of human resource among teachers so as to be able to provide quality psychosocial support. This will build competency among teachers to provide quality emotional psychosocial support which is lacking. The study recommends based on the findings the need to enhance teachers‟ especially female teachers to provide support especially emotional support therefore building competency among affected girls. Infected or affected girls who receive emotional support will be able to realize their potential in school and become self actualized individuals